Transcatheter Aortic Valve Implantation for Patients with Severe Aortic Stenosis - Nishioka, Toshihiko; Sasaki, Hideki; Shiota, Takahiro; Sasaki, Osamu (The Journal of Japanese College of Angiology, 2013)
Surgical aortic valve replacement is a gold standard therapy for severe aortic stenosis (AS). However, in the clinical setting, at least 30% of symptomatic patients with severe AS do not undergo surgery for replacement of the aortic valve, due to advanced age, severe left ventricular dysfunction, or the presence of multiple comorbidities. Transcatheter aortic valve implantation (TAVI) is a new procedure, developed as an alternative less invasive therapy of severe AS in patients who are not considered to be suitable candidates for surgery. Currently 2 valve systems, the Edwards SAPIEN system and the CoreValve system, are clinically available. The operators have to be extremely cautious during positioning and implantation of the valve because of aortic stenting under heart beating for calcified aortic valve. Recent results of clinical trials are reported and this article reviews clinical outline of TAVI.